Consulting report – Agencia B12 – launching of comparatodo in Perú - Flores Sempertegui, Gerardo Junior; Solís Pezzia, Diego Armando (Pontificia Universidad Católica del Perú, 2018)
Agencia B12 is a Spanish company specialized in digital marketing with offices in Spain, Mexico, Colombia and Peru. The firm has innovation at its core, and constantly develops tailor-made digital and traditional marketing strategies for its clients based on four values: innovation, passion, integrity and trust. Agencia B12 works primarily with clients in the telecommunications industry, and most of its revenue come from large players in their respective regions (such as Movistar, Claro and Entel in Peru). Given its highly concentrated client portfolio, Agencia B12 constantly seeks new business ventures to diversify their sources of revenue. As part of the firm’s diversification efforts, Comparatodo, a Price Comparison Website (PCW), was developed internally to benefit from such a growing and attractive industry (PCW). Comparatodo is currently operating in Spain, and Agencia B12 is planning to expand the website’s presence in other Latin American countries, starting in Peru. This report conducts an extensive research about Peru’s most promising industries and products for Comparatodo based on market size, pricing, and complexity of sales. Additionally, an analysis of direct and indirect competitors in Peru was conducted. As a result, the proposed solution is to first position Comparatodo as a PCW player in the telecommunications and financial services industry in Peru. The implementation plan is to be executed in 17 weeks and it involves different business units and personnel in the organization responsible for launching and maintaining Comparatodo. The key enablers supporting Comparatodo’s expansion in Peru are: already developed platform in Spain, internal IT department, experienced staff, extensive knowledge of digital marketing, few competitors, and opportunities in multiple industries.

Agencia B12 es una compañía española especializada en marketing digital con oficinas en España, México, Colombia y Perú. La empresa tiene como enfoque principal la innovación y desarrolla constantemente estrategias de marketing digital y tradicional a la medida para sus clientes en base a cuatro valores: innovación, pasión, integridad y confianza. Agencia B12 trabaja principalmente con clientes de la industria de telecomunicaciones y la mayoría de sus ingresos provienen de los jugadores más grandes en las regiones donde opera (como Movistar, Claro y Entel en Perú). Dada su cartera de clientes altamente concentrada, Agencia B12 se encuentra en la búsqueda de nuevos negocios para diversificar sus fuentes de ingresos. Como parte de los esfuerzos de diversificación de la empresa se ha desarrollado de manera interna Comparatodo, un sitio web de comparación de precios, con el fin de beneficiarse de esta industria tan atractiva y en crecimiento. Comparatodo opera actualmente en España y la empresa planea expandir su presencia en otros países de Latinoamérica, iniciando en Perú. Este reporte realiza una extensa investigación de las industrias y productos con mayor promesa en el Perú para Comparatodo en función a su tamaño del mercado, precios y complejidad de ventas. Además, se realizó un análisis de competidores directos e indirectos en el mercado peruano. Como resultado, la solución propuesta es posicionar a Comparatodo como un sitio web de comparación de precios en la industria de servicios financieros y telecomunicaciones en Perú. El plan de implementación consta de 17 semanas e involucra a diferentes unidades de negocio y personal de la empresa responsable del lanzamiento y mantenimiento de Comparatodo. Los habilitadores claves que respaldan la expansión de Comparatodo en Perú son: contar con la plataforma ya desarrollada en España, departamento de TI interno, personal experimentado, amplio conocimiento de marketing digital, poca competencia y oportunidades en diversas industrias.
Keywords: Mercadeo por internet; Telecomunicaciones; https://purl.org/pe-repo/ocde/ford#5.02.04